The Perception of Adolescents’ Encounter With a Flipped Learning Intervention in Norwegian Physical Education - Østerlie, Ove; Kjelaas, Irmelin (Frontiers in Education, 2019)
Objective: The discrepancy between observed and suggested levels of physical activity among adolescents urges society to obtain more knowledge and insight into how physical education (PE) in school can be beneficial for all individuals. The purpose of the present study was to examine the perceptions of adolescents of a flipped learning (FL) framework, applied to enhance student motivation and learning in PE. Methods: Ten students, from 13 to 17 years of age, were recruited from one secondary school and one upper secondary school from two different counties in Norway during the spring of 2016. The data were generated using semi-structured interviews, reduced, analysed and interpreted by constructivist grounded theory and stepwise-deductive induction traditions through constructivist and situated learning lenses. Results: It was demonstrated that the video format is preferred as preparation material over text material, that instructions on class activities are preferably given in the preparation material and not in class, and that the students did not report any negative aspects of FL. The students showed a positive perception of preparing for PE classes if the preparation material is in the form of a video, and if it has a clear connection to the upcoming class content and outcome aim(s). FL has a positive effect on student understanding and learning in PE, and FL produces a positive change in how students value PE. Conclusion: A clearly positive perception of FL in PE was demonstrated. FL seems to facilitate deep learning in PE, facilitated by motivation, knowledge, and the nature of the learning framework.